MANUSIA DAN TEKNOLOGI - Yasmina Maulida Mumtaz; Muhammad Riski Faozan; Nurul Mubin (JOURNAL SAINS STUDENT RESEARCH, 2025)
Technological advancements have influenced every aspect of human existence, bringing both conveniences and challenges. Overall, innovations in the internet, smartphones, artificial intelligence, and the Internet of Things have improved communication, work, education, and entertainment. Although the implementation of automation and AI in professional environments can boost productivity, it may also alter certain job roles and require new adaptive skills. From a social perspective, communication technologies facilitate global connectivity, yet they diminish the closeness typically experienced in face-to-face interactions. Moreover, growing reliance on technology can undermine cognitive abilities such as critical thinking, memory, and analytical skills due to the ease of access to information. Conversely, when managed prudently, emerging technologies can offer opportunities for learning and creativity. Effectively harnessing technology highlights the importance of balancing control with the emotional, cognitive, and social dimensions of life. Preserving human values alongside technological advancement underscores the necessity for digital literacy and responsible use of technology.